Synthesis of novel C-2 substituted imidazoline derivatives having the norbornene/dibenzobarrelene skeletons - Capan, Irfan; Servi, Suleyman (Arkat Usa Inc, 2018)
Novel imidazoline derivatives were synthesized from the norbornene and dibenzobarrelene skeletons which were obtained by the Diels-Alder reactions of anthracene and cyclopentadiene with the different dienophiles, such as fumaronitrile and fumaric acid. Synthesis of the C-2 substituted imidazolines was performed with high yields from various dinitriles and diacyl dichlorides. [GRAPHICS] .
Keywords: Cycloadditions; imidazoline; norbornene; dibenzobarrelene; guanidine; amide